The proportion of HIV incidence due to unsafe injections, unsafe blood transfusions and mother to child transmission in rural Masaka, Uganda - White, Richard G.; Kedhar, Anusha; Orroth, Kate K.; Biraro, Sam; Baggaley, Rebecca; Whitworth, Jimmy; Korenromp, Eline L.; Boily, Marie-Claude; Hayes, Richard J. (Proc Natl Acad Sci USA, 2007)
To estimate the proportion of all-age HIV incidence attributable to unsafe injections, unsafe blood transfusions and mother-to-child transmission (MTCT) in rural Masaka, Uganda, during the early 1990s.Observed HIV incidence and prevalence, and injection and transfusion rates were calculated using data from a general population cohort study in Masaka (1989-2000). Injection and blood transfusion safety was estimated from observational surveys within Uganda and East Africa. HIV transmission probabilities were estimated from scientific literature review. Model: A model was used to estimate the incidence via unsafe injections (assuming random or age-dependent mixing of injection equipment) and unsafe transfusions. An age-specific model of fertility was used to estimate the incidence via MTCT.Unsafe injections accounted for 5.1% [95% uncertainty bounds (UB) 0.0-10.3] or 12.4% [95%UB 0.0-27.0] of all-age HIV incidence in the random and age-dependent mixing scenarios respectively. Unsafe blood transfusions accounted for 0.4% [95%UB 0.2-0.6], and MTCT accounted for 23.4% [95%UB 15.3-31.5]. 64-71% of all-age HIV incidence was left unexplained by these three routes of transmission. Among 13+ year olds, unsafe injections accounted for 1.4% [95%UB 0.0-2.8] or 12.1% [95%UB 0.0- 26.5] of HIV incidence in the random and age-dependent mixing scenarios respectively. Unsafe blood transfusions accounted for 0.3% [95%UB 0.1-0.4], leaving 87.6-98.3% of HIV incidence left unexplained by these three routes of transmission.This study does not support the hypothesis that unsafe injections or blood transfusions played a major role in HIV transmission in this population during the study period. The safety of both injections and transfusions should be improved to reduce HIV transmission via these routes still further, but particular efforts should be made to reduce the larger proportion of HIV transmission due to MTCT, and among 13+ year olds, the unexplained incidence, presumably primarily due to sexual transmission.